Propuesta de materiales educativos para desarrollar el área de personal social en infantes de 2 años - 2017 - Fabian Huaman, Nanci Indelicia (2021)
The research is aim to bring an approach with educational materials in order to develop the social personnel area, with 2 years infants, through a descriptive investigation, to confirm that to educative materials have great importance in a learning motivation. We affirm the teacher creativity is essential to provide the most appropiate and innovative educational material, thus achieving the desired meaningful learning. Regarding this data, what we are trying to do is solve the thousand doubts from the teachers when trying to know the kind of materials necessary for a lesson plan session in the social personnel área and learning and meaning degree that it is 2 years infants therefore, we will propose wich educational materials are suitable, novelty and adequate for the development of the social personnel área. So in this way propose their implementation according to the needs and interests of this age infants.